Non-verbal amusement in later life: An analysis of age-related shifts in humor comprehension - Girija, P C; Nayana, Narayanan; Hashim, Heena (International journal of health sciences, 2025)
Humor is the ability to understand and express what is funny, serving a crucial social function, fostering connection, relieving stress, and navigating awkward situations encompassing language, gesture, visual imagery, and situation management. This study aims to investigate the impact of aging on non-verbal humor processing in Malayalam-speaking adults. 150 healthy Malayalam-speaking adults, aged 31-80 years, were divided into five age groups with all meeting the criteria of normal cognitive function with humor exposure. Participants underwent humor assessment using a specially developed material consisting of non-verbal stimuli, with funniness responses being rated using funniness rating scales. Statistical analysis involving mean scores, Kruskal-Wallis, and Mann-Whitney U test with Bonferroni corrections was used to compare humor processing across age groups. The study revealed a significant age-related decline in humor processing, particularly after the age of 60, with cognitive factors like working memory, processing speed, and cognitive flexibility significantly impacting the humor comprehension. The most intriguing part of the study was that participants in the age range of 51-60 years performed better compared to other age groups.